Optimization of cutting parameters for drilling carbon-epoxy fabrics laminates with different fiber orientations - Nor Farah Huda bt Abd Halim (Kulliyyah of Engineering, International Islamic University Malaysia, 2013)
The automotive, aerospace, manufacturing and electronics industries have demonstrated an increased demand for critical components made of composite materials due to their unique properties. Machining process especially drilling is usually widely employed in this industry. However, the quality of drilled hole is the main issue since the drilling process usually occurs at the end of the manufacturing process. In this work, a study on cutting parameters such as the speed and feed rate, as well as the laminates configuration were investigated. This research has investigated the parameters that affect the damage mechanism i.e.: peel-up delamination and push-down delamination and the force on the carbon-epoxy laminates during drilling process on the ANILAM CNC machine. Six types of fabrics laminates stacking sequences which are 0°/0°/0°/0°, 45°/45°/45°/45°, 45°/0°/45°/0°, 0°/45°/0°/45°, 0°/0°/45°/45° and 45°/45°/0°/0° have been tested in this research. The force evolutions on each layer have also been studied. This study comprised of identification of optimum parameter and suitable laminates configuration to improve the force, peel-up and push-down delamination. The General factorial was employed to design the number of experiment. Mathematical models were developed for the output responses of peel-up delamination (Fdin), push-down delamination (Fdout) and force (N). A desirability of 98.5% was obtained with the peel-up delamination (Fdin) value of 1.0479, push-down delamination (Fdout) value of 1.00098 and force (N) value of 2.228N. The optimized values were experimentally verified and found to be different 2% to 11% from the predicted values. In the second phase of experimental work, optimum parameters were employed to ensure a clearer view on the force evolution on each layer of the fabrics laminates and its' effects on the damage mechanism.